Liraglutide in type 2 diabetes: from pharmacological development toclinical practice - Rossi, M. C.; Nicolucci, A. (Acta Biomedica Atenei Parmensis, 2009)
The novel drug class of GLP-1 analogues is extremely promising, since existing evidence suggests they can address many of the unmet needs of diabetes treatment, i.e. long-term efficacy, low risk of hypoglycemia, cardiovascular protection, weight loss, long-term safety and tolerability. Besides the already available exenatide, liraglutide is expected to arrive soon on the market. It is a human GLP-1 analogue with high homology (97%) to native hormone. A comprehensive phase III evaluation consisting of six randomized clinical trials - the “Liraglutide Effect and Action Diabetes (LEAD) program” - was recently completed,  involving 6500 people seen in 600 sites in 41 countries worldwide. Aim of the LEAD program was to evaluate efficacy and safety of liraglutide as monotherapy and in combination with commonly used antidiabetic drugs. In all studies, once-daily liraglutide was well tolerated, significantly improved metabolic control, and reduced body weight, with low rates of hypoglycemia. Transient nausea was the most common side effects. Additional beneficial effects of liraglutide on beta-cell function, systolic blood pressure, and cardiovascular risk were also documented. If these encouraging results will be confirmed by long-term studies, liraglutide will acquire a prominent role among the main therapeutic options not only as add-on treatments in case of secondary failure, but also as an early strategy to reduce the burden of diabetes and its complications.